Uptake and factors associated with HIV self-testing among rural dwellers in Ibadan, Nigeria - Margaret O. Akinwaare; Mary T. Omolewa-Ogunsola (Public Health, 2026)
Background: HIV self-testing (HIVST) is an innovative strategy designed to expand access to HIV testing by allowing individuals to test privately and conveniently, thereby addressing stigma, time constraints, and limited access to facility-based services. Despite its potential, uptake among rural populations in Nigeria remains unclear. This study assessed the uptake of HIV self-testing and factors influencing its utilization among rural dwellers in Ibadan, Oyo State, Nigeria. Methods: A cross-sectional descriptive quantitative design was employed among 218 adults selected through multistage sampling from Ajibode (Akinyele LGA) and Omi Adio (Ido LGA). Data were collected using an adapted structured questionnaire with established validity and reliability (Cronbach’s α > 0.70). Analysis was conducted using SPSS version 27. Descriptive statistics summarized uptake levels, while chi-square tests and logistic regression identified associated factors and predictors at a 0.05 level of significance. Results: Results revealed extremely low uptake of HIVST, with only 7.8% of respondents having ever used a self-testing kit. Overall, 91.3% demonstrated low uptake based on composite scoring. Major barriers included lack of knowledge on kit use, distrust of results, preference for facility-based testing, and poor accessibility. However, 66.5% expressed willingness to self-test if kits were readily available. Education was the only sociodemographic factor significantly associated with uptake (χ² = 5.151, p = 0.047). Logistic regression identified significant predictors including planning for the future/health responsibility (AOR = 3.362, p = 0.006), encouragement from sexual partners (AOR = 2.545, p = 0.013), and peer encouragement (AOR = 2.384, p = 0.016). Age, gender, employment status, and number of sexual partners were not significantly associated. Conclusion: HIV self-testing uptake among rural dwellers in Ibadan is markedly low despite high willingness. Improving health education, strengthening trust, expanding kit accessibility, and leveraging social support networks are essential to enhance HIVST adoption in rural Nigerian settings.